Imaging in neuroendocrine tumors: an update for the clinician. (May 2015) - Maxwell, Jessica E; Howe, James R
Neuroendocrine tumors are a heterogeneous group of neoplasms that are best worked up and managed using a variety of clinical and imaging studies. They are often diagnosed after they have already metastasized, though this does not necessarily preclude an attempt at curative surgical treatment or surgical debulking. Tumor burden assessment often requires use of multiple imaging modalities including computed tomography, magnetic resonance imaging and ultrasound. Somatostatin receptor-based imaging is also of great utility in looking for primaries and determining the extent of metastatic disease. This paper will review the most common imaging modalities used in the diagnosis and treatment of neuroendocrine tumors.